A New Method to Investigate How Mechanical Loading of Osteocytes Controls Osteoblasts - Vazquez, Marisol; Evans, Bronwen A. J.; Riccardi, Daniela; Evans, Sam L.; Ralphs, Jim R.; Dillingham, Christopher Mark; Mason, Deborah J. (Frontiers in Endocrinology, 2014)
Mechanical loading, a potent stimulator of bone formation, is governed by osteocyte regulation of osteoblasts. We developed a 3D in vitro co-culture system to investigate the effect of loading on osteocyte-osteoblast interactions. MLO-Y4 cells were embedded in type I collagen gels and MC3T3-E1(14) or MG63 cells layered on top. Ethidium homodimer staining of 3D co-cultures showed 100 % osteoblasts and 86 % osteocytes were viable after 7 days. Microscopy revealed osteoblasts and osteocytes maintain their respective ovoid/pyriform and dendritic morphologies in 3D co-cultures. Reverse-transcriptase quantitative polymerase chain reaction (RT-qPCR) of messenger ribonucleic acid (mRNA) extracted separately from osteoblasts and osteocytes, showed that Podoplanin (E11), osteocalcin (OCN) and runt-related transcription factor 2 (Runx2) mRNAs were expressed in both cell types. Type I collagen (Col1a1) mRNA expression was higher in osteoblasts (P<0.001), whereas alkaline phosphatase (ALP) mRNA was higher in osteocytes (P=0.001). Immunohistochemistry revealed osteoblasts and osteocytes express E11, type I pro-collagen and connexin 43 (CX43) proteins. In preliminary experiments to assess osteogenic responses, co-cultures were treated with human recombinant bone morphogenetic protein 2 (BMP-2) or mechanical loading using a custom built loading device. BMP-2 treatment significantly increased osteoblast Col1a1 mRNA synthesis (P=0.031) in MLO-Y4/MG63 co-cultures after 5 days treatment. A 16-well silicone plate, loaded (5 min, 10 Hz, 2.5 N) to induce 4000-4500 με cyclic tension within gels increased prostaglandin E2 (PGE2) release 0.5 hr post-load in MLO-Y4 cells pre-cultured in 3D collagen gels for 48 hr, 72 hr, or 7 days. Mechanical loading of 3D co-cultures increased type I pro-collagen release 1 and 5 days later. These methods reveal a new osteocyte-osteoblast co-culture model that may be useful for investigating mechanically-induced osteocyte control of osteoblast bone formation.